Stabilization of ion selectivity filter by pore loop ion pairs in an inwardly rectifying potassium channel - Yang, Jian (The National Academy of Sciences of the USA, 1997)
Ion selectivity is critical for the biological functions of voltage-dependent cation channels and is achieved by specific ion binding to a pore region called the selectivity filter. In voltage-gated K(+), Na(+) and Ca(2+) channels, the selectivity filter is formed by a short polypeptide loop (called the H5 or P region) between the fifth and sixth transmembrane segments, donated by each of the four subunits or internal homologous domains forming the channel. While mutagenesis studies on voltage-gated K(+) channels have begun to shed light on the structural organization of this pore region, little is known about the physical and chemical interactions that maintain the structural stability of the selectivity filter. Here we show that in an inwardly rectifying K(+) (IRK) channel, IRK1, short range interactions of an ion pair in the H5 pore loop are crucial for pore structure and ion permeation. The two residues, a glutamate and an arginine, appear to form exposed salt bridges in the tetrameric channel. Alteration or disruption of such ion pair interactions dramatically alters ion selectivity and permeation. Since this ion pair is conserved in all IRK channels, it may constitute a general mechanism for maintaining the stability of the pore structure in this channel superfamily.